EFFECT of Jatrophaurens (Euphorbiaceae) and Lantana camara (Verbenaceae) on Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) - Vinasco A., Natalia; Salazar P., Estefany; Soto G., Alberto; Mejía G., Luis Fernando; Dussan L., Carmen (Revista de Ciencias Agrícolas, 2015)
Trialeurodes vaporariorum is one of the main pests associated to horticulture crops, and its control is generally based on the use of agrochemicals. The objective of this study was to evaluate the effect of J. urens and Lantana camara extracts and Alisin® commercial product on the developmental stages of T. vaporariorum under laboratory conditions. In eggs, the ethanolic extract of L. camara and the acetonic extract of J. Urens caused mortality above 33%; in nymphs, the ethanolic extracts of both species caused mortality greater than 94%, while in adults, the acetonic extracts of J. urens and the acetonic+ether extracts of L. camara caused mortality over 80%. Alisin® showed a similar behavior to the acetonic extracts of J. urens and the acetonic+ether extracts of L. camara for the control of pest adults.